Gospodarowanie majątkiem komunalnym - wybrane obszary problemowe - Wartalska, Magdalena (Management of Communal Property - Selected Problematic Areas, 2006)
This article is dedicated to problems from the area of managing communal property. Communal assets make a permanent base for economic self-government of territorial self-governing units. They are also a base for accomplishment of public tasks, which directly influences the choices of methods and forms of property usage, as well as the owner's decisions made by local authorities. Management of self-government property is a multidimensional field, which requires using management techniques adequately to the often changing conditions of running a business. Contemporary economic and legal circumstances make it necessary to reorient the processes of self-government's property management, especially regarding the time factor. In search of new, most effective solutions local authorities more often see the need of full and conscious coordination of tasks, decisions and organizational undertakings made in aid of the rationalization of this process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 659-669